Communities and Households in the Greater American Southwest : New Perspectives and Case Studies - Stokes, Robert James, 1961- (Book collections on Project MUSE., 2019)
"New research on human organization in the American Southwest, examining families, households, and communities in the Ancestral Puebloan, Mogollon, and Hohokam cultural areas from the earliest habitation to the twenty-first century. Using historical data, dialectic approaches, problem-oriented and data-driven analysis, and ethnographic and gender studies methodologies "--Provided by publisher